2007
DOI: 10.1103/physrevb.75.012404
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the timescales in picosecond remagnetization experiments

Abstract: In femtosecond demagnetization experiments, one gains access to the elementary relaxation mechanisms of a magnetically ordered spin system on a time scale of 100 fs. Following these experiments, we report a combined micromagnetic and experimental study that connects the different regimes known from all-optical pump-probe experiments by employing a simple micromagnetic model. We identify spin-wave packets on the nanometer scale that contribute to the remagnetization process on the intermediate time scale betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
77
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 31 publications
1
77
1
1
Order By: Relevance
“…One can, for example, mention that during the femtosecond demagnetisation the electron temperature is often raised up to the Curie temperature 22,24 . At this moment, the high frequency THz spinwaves 35,36 including the Stoner excitations 30 contribute. At the same time, the transverse relaxation is related to the homogeneous precessional mode.…”
Section: Introductionmentioning
confidence: 99%
“…One can, for example, mention that during the femtosecond demagnetisation the electron temperature is often raised up to the Curie temperature 22,24 . At this moment, the high frequency THz spinwaves 35,36 including the Stoner excitations 30 contribute. At the same time, the transverse relaxation is related to the homogeneous precessional mode.…”
Section: Introductionmentioning
confidence: 99%
“…This discovery lead to intense theoretical [2][3][4][5][6][7][8][9] and experimental [10][11][12][13][14][15][16] investigations on the origin of these ultrafast magnetization dynamics, however, the dominant microscopic mechanism is still under debate.…”
mentioning
confidence: 99%
“…[17][18][19][20] However, in ultrafast magnetization reversal the high-energy electrons generated by the laser field decay into the lower-energy magnon excitations. [22][23][24] In both cases spin-orbit coupling (SOC) is responsible for the transfer of the angular momentum to the lattice through different scattering mechanisms such as magnon-magnon, magnon-phonon, magnon-impurity scattering, and so on, where each process has a different relaxation time. 27,28 The Landau-Lifshitz-Gilbert (LLG) equation with a phenomenological damping constant α is commonly employed to describe magnetization dynamics of small-angle precessional switching.…”
mentioning
confidence: 99%
“…12 In current devices the switching speeds have reached a point where dynamical effects are becoming very important [12][13][14][15][16] Magnons are created in fast (field driven) as well as ultrafast (laser induced) magnetization reversal processes. [17][18][19][20][21][22][23][24][25][26] The former case is of particular interest for current device applications. It is found that above some threshold magnetic field the uniform precessional mode, i.e., the k = 0 magnons decay into nonuniform magnons (k = 0), i.e., the Zeeman energy stays in the magnetic subsystem and scatters between magnon modes.…”
mentioning
confidence: 99%
See 1 more Smart Citation